2021
DOI: 10.3390/genes12060942
|View full text |Cite
|
Sign up to set email alerts
|

Short Time-Series Expression Transcriptome Data Reveal the Gene Expression Patterns of Dairy Cow Mammary Gland as Milk Yield Decreased Process

Abstract: The existing research on dairy cow mammary gland genes is extensive, but there have been few reports about dynamic changes in dairy cow mammary gland genes as milk yield decrease. For the first time, transcriptome analysis based on short time-series expression miner (STEM) and histological observations were performed using the Holstein dairy cow mammary gland to explore gene expression patterns in this process of decrease (at peak, mid-, and late lactation). Histological observations suggested that the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…Pizzi et al ( 36 ) suggested that genes with similar expression have similar biological functions and work in concert. Fan et al ( 37 ) used STEM to examine genes associated with mammary development at peak, mid and late lactation in dairy cows and found that DEGs are mainly involved in apoptosis and energy metabolism, suggesting the reliability of the STEM analysis method. In the present study, we obtained four colored Clusters with the same trend (25, 24, 8, and 35) by STEM analysis of DEGs cross PHPO axis in Tan sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Pizzi et al ( 36 ) suggested that genes with similar expression have similar biological functions and work in concert. Fan et al ( 37 ) used STEM to examine genes associated with mammary development at peak, mid and late lactation in dairy cows and found that DEGs are mainly involved in apoptosis and energy metabolism, suggesting the reliability of the STEM analysis method. In the present study, we obtained four colored Clusters with the same trend (25, 24, 8, and 35) by STEM analysis of DEGs cross PHPO axis in Tan sheep.…”
Section: Discussionmentioning
confidence: 99%
“…The read counts of the circRNAs were converted into FPKM (expected number of Fragments Per Kilobase of transcript sequence per Millions of base pairs sequenced). Next, the STEM clustering method was utilized to analyze the expression trend of circRNAs from the budding to the fading of Rhododendron delavayi Franch [ 48 , 49 ]. For the STEM analysis, default parameters were used.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptome sequencing provides a high-throughput method for studying the molecular mechanisms of mammary gland development. Currently, a large number of studies have been carried out on transcriptome analysis of mammary gland or milk, involving goats (Crisà et al, 2016;Shi et al, 2016;Li et al, 2020), sheep (Paten et al, 2015;Wang et al, 2020), cattle (Bionaz et al, 2012;Zheng et al, 2018;Bhat et al, 2019;Fan et al, 2021), and pig (Shu et al, 2012;Palombo et al, 2018) at different stages of mammary gland development. Researches on the expression profile of mammary gland tissue after cessation of milking provide important clues to the molecules that may mediate epithelial cell death and tissue remodeling during involution (Clarkson et al, 2004;Stein et al, 2004;Shi et al, 2016).…”
Section: Transcriptome Profiling Of the Nonlactating Mammary Glands O...mentioning
confidence: 99%